KARAKTERISTIK SIFAT TARIK DAN MODE PATAHAN KOMPOSIT POLYESTER BERPENGUAT SERAT TAPIS KELAPA - I Made Astika; I Gusti Komang Dwijana (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
The purpose of this study is to investigate the mechanical properties i.e. tensile strength of composites coconut filter fiber. In the future this material can be used to replace the wood, bamboo and gipsun which are high price and lower water resistance.The research material made with coconut filter fiber as reinforcement and matrix resin unsaturated polyester (UPRs) type Yukalac BQTN 157, with 1% hardener types MEKPO (Methyl Ethyl Ketone Peroxide) and fiber treatment by  0.5% KMnO4. Production methods are poltrusion and the variations of fiber volume fraction are 20, 25 and 30% and fiber length are 5, 10 and 15 mm. Testing of mechanical properties is tensile test (ASTM D3039-76) The results of research show  that  the longer of fiber and the bigger of fiber volume fraction, the higher of tensile strength are obtained. The fracture mode are overload, debonding, pullout and crack deflection